Galleria mellonella as an in vivo skin model of superficial infections caused by Malassezia globosa (2021)
Malassezia globosa is a lipid-dependent yeast that is part of the commensal microbiota of human skin and is related to the development of highly prevalent dermatological disorders such as pityriasis versicolor, seborrheic dermatitis, dandruff, atopic dermatitis, and folliculitis. Furthermore, skin colonization by Malassezia yeasts is considered a risk factor in developing systemic infections. Little is known about the host-pathogen interaction of these types of infections, precisely what factors trigger the pathogenicity of yeast. For this reason, it is necessary to implement in vivo models such as Galleria mellonella larvae. These present many advantages compared to other models: inexpensive, easy to use, do not require approval from ethics committees, the components of their cellular and humoral immune systems are similar to those involved in the innate immune response against fungal pathogens in mammals (such as phagocytic cells) and present a cuticle that simulates the barrier function characteristic of the stratum corneum. This work aims to implement a methodology that allows using G. mellonella as an in vivo model for skin infections caused by M. globosa. For this, three pilot studies and a trial were carried out. The effect of different levels and methodologies of abrasion (1 to 5) and inoculation was evaluated through histology, hemocyte count, and daily observation. It was found that it is possible to successfully establish superficial infection with M. globosa in the integument of G. mellonella larvae under a cuticle abrasion level 4 in less than 72 hours using an abrasion device. Also, a new score of melanization of the lesion was proposed.